When customers strike back: examining the impact of psychological contract violation on customers' switching behaviour - David Amani (African Business Management Journal)
Although the psychological contract has garnered attention from scholars in the social sciences, little is known about its implications from a marketing perspective. This study aims to investigate the mediating role of customer-brand disidentification between psychological contract violation and customers' switching behaviour. It represents an initial attempt to explore psychological contract violation from the perspective of the service domain in emerging economies, contributing to theoretical and practical discussions on the factors influencing customers' switching behaviour. The study utilised a quantitative-based cross-sectional design involving 399 customers from three selected pay television companies in Tanzania's media industry. Data were collected using a structured questionnaire and analysed using structural equation modelling. The findings reveal that psychological contract violation influences customers' switching behaviour when mediated by customer-brand disidentification. Consequently, if disidentification is not managed effectively, customers disengage from their relationship with the service providers and opt for alternative providers. The study suggests that service providers should proactively identify signs of psychological contract violation and implement necessary measures to address them, thereby mitigating the likelihood of customers resorting to switching behaviour.